Measuring undergraduate nursing students' knowledge of Christian, Islamic, and Hindu death rituals: A national study - Corbally, Melissa (My University, 2025)
Background: Globally, research indicated undergraduate nursing students have limited knowledge, in caring for people at the time of death. With increasing immigrant populations, undergraduate nursing students and nurses seeking to provide culturally competent care lacked specific knowledge regarding the death rituals of other religions which presents a major knowledge gap that must be addressed. This study measured undergraduate nursing students' knowledge of specific death rituals as practised by three world religions (Christianity, Islam and Hinduism) in the Republic of Ireland. Aim: The current study aimed to measure undergraduate nursing students' knowledge of specific death rituals as practised by three world religions (Christianity, Islam, and Hinduism). Design: This study used a quantitative descriptive cross-sectional design. Participants: Nursing students from all 13 higher education institutions (HEIs) registered with the Nursing and Midwifery Board of Ireland were invited to participate. Out of these, eight HEIs consented, representing a total of 5050 undergraduate nursing students. From this pool, 414 students, spanning from all nursing and midwifery programs from all four provinces of Ireland, participated in the study. Methods: A 23-item knowledge survey, The Knowledge Questionnaire (KQ) was developed with input from experts and validated for accuracy, relevance, essentiality, and reliability. Further reliability testing of the tool was done in this study. Results: The Knowledge Questionnaire (KQ) was found to be reliable showing a Cronbach's alpha coefficient of 0.873 in the national study. The findings highlighted a significant lack of knowledge regarding death rituals across the religious groups. Most students reported seeking information about these rituals from sources outside of formal nursing education. Conclusion: Based on these results, the authors strongly recommends the inclusion of mandatory cultural education in nursing programs to better prepare students for end-of-life care in diverse cultural contexts. Relevance to clinical practice: This study provides an informed starting point from which specifically tailored education programmes could be developed and implemented. The goal is to foster culturally competent care in both clinical and academic settings to meet the needs of increasingly culturally diverse patient populations in a variety of health care settings nationwide.
PUBLISHED
Keywords: Nursing education; Religion; Death rituals; End-of-life care; Nursing practice; Cultural competency; Cultural knowledge; Inclusive Society; Nursing Education; Culture; Health